Tau isoforms drive differential transposable element and gene expression: Molecular and cell biology/tau. (7th December 2020) - Grundman, Jennifer Ann; Spencer, Brian; Rissman, Robert A.
Abstract: Background: Tau isoform overexpression differs in several neurodegenerative. For instance, Alzheimer's disease (AD) is characterized by overexpression of 3R and 4R tau, while progressive supranuclear palsy (PSP) and Pick's disease (PiD) show overexpression of 4R and 3R tau, respectively. Tau's role in nuclear processes have only just begun to draw focus, with studies showing it binds protectively to DNA and can contribute to heterochromatin relaxation (Sultan et al., 2011; Frost et al., 2014). Recently, tau has been implicated in activating transposable elements (TEs), which are normally repressed and can trigger immune responses and genomic stress (Guo et al., 2018; Sun et al., 2018). Yet tau isoforms' role in these phenomena has not been examined and may reveal new details of tau‐driven pathology. Method: SH‐SY5Y cells were differentiated and infected with lentiviral constructs of 0N3R tau, 2N4R tau, a 1:1 split of 0N3R and 2N4R, or a control construct before treatment with DMSO or Aβ‐42 oligomers. DNA damage and tau translocation were assessed using immunofluorescence and immunoblotting. RNA sequencing was performed and differential gene and TE expression measured using DESeq2 and TEtranscripts, respectively. For all cell‐based experiments, N=3. Further analysis was performed on RNA‐sequencing data of AD, PSP, and control patients (N=20 for each group), which is publicly available through AMP‐AD Knowledge Portal (doi:10.1038/sdata.2016.89). Result: Results revealed more significant differences in gene and TE expression in the presence of overexpressed 4R tau than in overexpressed 3R tau alone. The most dysregulated TEs were ERVs, though all samples overexpressing tau showed dysregulation of LINEs. Notably, 4R tau overexpression also showed downregulation of nuclear processes and the ribosome. Conclusion: These results provide novel insights into the effects of different tau isoforms and their interactions with Aβ‐42 and is the first study to show that tau isoforms uniquely affect TE expression. Our study bolsters support for future research into tau isoforms and tau‐driven activation of TEs and potential therapeutics that target them.